INTERNET DAN INFLASI: CROSS-COUNTRY PANEL ANALYSIS ATAS 5 NEGARA DI ASIA - Anhar Fauzan Priyono (Universitas Negeri Medan, 2016)
The objective of this research is to understand the effect of internet utilization,proxied by numbers of internet user to inflation rate. Several other factors are alsobeing considered, which are growth of money supply, exchange rate, and world oilprice. There are China, India, Japan, Indonesia, and South Korea, consecutivelyrepresent top five countries with the biggest internet users in Asia to be observed.Pooled Least Square with Panel Corrected Standard Error has been employed interms of analysing inflation's behavior of those countries. The main finding of this research is that inflation and numbers of internet user are negatively correlated, while the causal effect is statistically not significant. This is most probable, since utilization of internet is still dominated by web surfing, social media, and online games. On the other hand, money supply, exchange rate, and world oil price has a positive relationship with inflation. Those findings are true for all the countries being observed.